Causes and complications related to the use of drains: A literature review (Research, Society and Development, 2023)
Introduction: The recovery of the surgical patient depends on numerous factors, but mainly on the occurrence of complications, thus increasing the risk of reoperation, increasing the length of hospital stay and increasing morbidity and mortality. Objective: To identify the causes and complications related to the use of drains. Methodology: This study is an integrative literature review. The elaboration of the methodological survey for the research was carried out in the period of April 2023, the databases used were the Latin American and Caribbean Literature in Health Science (LILACS), Nursing Database (BDENF) and Medical Literature Analysis and Retrieval System Online (MEDLINE), using Health Sciences Descriptors (DeCS), namely: Surgical wound infection; Surgical equipment and postoperative complications, being used in the English language to have a greater number of studies, being crossed with the Boolean AND operator. Results: The selected studies presented content on the relationship between infection associated with the implementation of drains, the surgical site and the functionality of drains and their care against the development of infections. With that, drainage, but precisely the thoracic insertion is considered a clinical practice most used among procedures. Conclusion: With this, the causes and complications related to the use of drains in surgical procedures, pointing out the causes such as the poor positioning of the drain, the lack of adequate monitoring by the health team and in relation to the complications, the risks of infections, even pleural effusion, due to extravasation of the liquid content to be drained.